Worker safety perception analysis of South Korean construction sites. Issue 2 (3rd April 2021) - Kwon, Yeong-Tak; Son, Seunghyun; Kim, Sunkuk; Ha, Sun-Geun; Son, Kiyoung
Abstract : Purpose. The aim of this article was to measure the safety perception level of workers on a South Korean construction site and investigate safety problems using the Nordic occupational safety climate questionnaire (NOSACQ-50). Methods. The survey was carried out via the NOSACQ-50 with 175 workers from five South Korean construction companies to evaluate their perception level. The results were then compared with the NOSACQ-50 criteria. Results. The safety perception of this South Korean construction site is high when compared with the NOSACQ-50 criteria. This high level was especially pronounced for the seventh dimension of the efficacy of the safety system, which showed the highest level among all dimensions. In addition, we suggested improvements and interventions to sustain a safety climate amongst workgroups. Conclusions. This study confirms that the seventh dimension showed the highest safety perception amongst all dimensions in South Korea. In the future, these findings can be utilized to develop an evaluation tool for the safety climate of the construction industry in South Korea.